2018
DOI: 10.1371/journal.pone.0208087
|View full text |Cite
|
Sign up to set email alerts
|

Adverse event detection by medical record review is reproducible, but the assessment of their preventability is not

Abstract: ObjectiveTo assess the reproducibility of adverse event evaluation by a medical record review committee.DesignCross-sectional reanalysis of medical records.InterventionReviewers re-examined fifty medical records of deceased patients regarding the presence of adverse events, their potential preventability and their possible contribution to death. Also we investigated the root causes of the preventable AEs. Differences between the first and second assessment were calculated.ResultsThe Kappa on the presence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…In a systemic and systematic perspective of a right clinical risk management, different methods, tools and actions are expected to revel risk sources, to provide useful evidences about the incident of adverse events, and therefore to reach a reduction and containment of the same [ 5 , 6 ]. These processes take advantage of proactive precise tools that hospitals experiment and use with different degrees of awareness, the main of which are safety briefings, focus groups, analysis and review of medical records, screening, observations, patient safety walkaround and global trigger tool [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a systemic and systematic perspective of a right clinical risk management, different methods, tools and actions are expected to revel risk sources, to provide useful evidences about the incident of adverse events, and therefore to reach a reduction and containment of the same [ 5 , 6 ]. These processes take advantage of proactive precise tools that hospitals experiment and use with different degrees of awareness, the main of which are safety briefings, focus groups, analysis and review of medical records, screening, observations, patient safety walkaround and global trigger tool [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the previous years, both committees used the same review procedure. Previous research showed the results of this internal MRR to be acceptably reliable 12…”
Section: Introductionmentioning
confidence: 72%
“…Man mĂ„ vaere varsom i vurderingen av hvor mange dĂždsfall som kan forebygges, da dette er vanskelig Ă„ fastslĂ„ (26)(27)(28). Kompleksiteten i moderne sykehusbehandling er et poeng, og man har funnet betydelig variasjon i undersĂžkernes vurdering (26,27). I en nyere publikasjon fra Canada blir det sagt at virkelig forebyggbare dĂždsfall er sjeldne (29).…”
Section: Resultaterunclassified